From genes to genomes : concepts and applications of DNA technology - Dale, Jeremy W. (Wiley - Blackwell, 2012)
The latest edition of this highly successful textbook introduces the key techniques and concepts involved in cloning genes and in studying their expression and variation. The new edition features: * Increased coverage of whole-genome sequencing technologies and enhanced treatment of bioinformatics. * Clear, two-colour diagrams throughout. * A dedicated website including all figures. Noted for its outstanding balance between clarity of coverage and level of detail, this book provides an excellent introduction to the fast moving world of molecular genetics.